Association between the posterior ocular contour pattern and progression of myopia in children: A prospective study based on OCT imaging. (12th August 2021) - Xu, Shengsong; Hu, Yin; Cui, Dongmei; Zhao, Feng; Jiang, Jinyun; Feng, Zhibin; Li, Cong; Li, Zhouyue; Yang, Xiao
Abstract: Purpose: This study aims to reveal the relationship between the posterior ocular contour and the subsequent progression of myopia in children. Methods: Children aged 8–12 years with myopia received baseline measurements and were instructed to wear their glasses every day and return for a follow‐up visit after one year. Axial length and other ocular parameters were measured using a noncontact biometer. The contour of the posterior eye was calculated and analysed based on images from spectral domain optical coherence tomography (SD‐OCT). Univariate and multivariate linear regression models were created to analyse the relationship between the contour of the posterior eye and the progression of myopia. Results: Baseline posterior ocular contour measurements correlated with baseline axial length and spherical equivalent refraction (SER) (all p < 0.05). Eyes that were more myopic tended to have a more prolate posterior ocular contour. Although the baseline contour of the retinal pigment epithelium (RPE) and chorioscleral interface (CSI) showed no significant relationship with the progression of myopia (all p > 0.05), interestingly, when the baseline contour of the RPE was more prolate than that of the CSI, the axial length increased during the following year ( R 2 = 0.62; p < 0.01). The multivariate model, when adjusted for other variables, further validated the independent role of this variable. Conclusions: The difference between the RPE and CSI contours correlated with the subsequent progression of myopia in children. This finding can help inform clinicians regarding the management of children at the onset of myopia and potentially provide an avenue for experimental research on the mechanism of myopia development.